ISLAMIC ARTS MUSEUM, MALAYSIA: EDUCATIONAL TOOL FOR REVIVING ARCHITECTURAL HERITAGE - Dilmi, Djamel (Journal of Islamic Architecture, 2013)
AbstractThe Islamic art and architecture have played a significant role in the development of historic cities in the Muslim world; they were developed through time in response to socioeconomic and cultural needs of the society. The paper will focus on the experience of the Islamic Arts Museum in terms of its role in raising public awareness about Islamic art and architecture through its building that combines modernity and heritage in unique Islamic architectural style and educational programs and activities that educate people about conservation of Islamic heritage. The aim of this essay is to present the experience of IAMM in promoting Islamic art and architecture in order to share experience as a successful model. To achieve this aim the existing conditions of this museum were examined in  terms of its building, decorated element, cultural activities  and  conservation  programs using  traditional  ways and  modern technologies.  A  broad  range  of information was collected from various sources and through a field survey carried out in the selected museum from modern country leading development in the Muslim world. The collected information was analyzed with particular regard to the special character. This paper is an attempt to address the important issues of educational programs that raise public awareness about heritage through interior design and display of artifact from different regions of Muslim world matters that have been raised in many museums around the world and it is hoped that it is going to be a significant contribution to the subject of reviving Islamic architecture in the modern world.Keywords: Islamic art and architecture, museum, modernity and heritage, conservation programs, educational activities.  AbstrakSeni  dan  arsitektur  Islam  telah  memainkan  peran  yang  sangat  penting  dalam  perkembangan  kota-kota bersejarah di dunia Muslim; dibangun sepanjang masa sebagai respon terhadap kebutuhan sosial ekonomi dan budaya dari masyarakatnya. Makalah ini akan difokuskan pada pengalaman Museum Seni Islam dalam perannya meningkatkan kesadaran  publik tentang  seni  dan  arsitektur Islam melalui arsitekturnya yang  memadukan modernitas dan warisan budaya Islam di dalam gaya arsitekturnya, program-program edukatif, dan aktivitas- aktivitas yang mendidik masyarakat mengenai pelestarian warisan budaya Islam. Tujuan dari makalah ini adalah untuk menyajikan pengalaman IAMM di dalam mempromosikan seni dan arsitektur Islam, dalam rangka berbagi pengalaman sebagai salah  satu  model yang berhasil. Untuk  itu, pembahasan mengenai museum ini akan meliputi bangunannya, elemen dekorasinya, aktivitas-aktivitas kulturalnya, dan program-program konservasi menggunakan cara-cara tradisional dan  teknologi modern. Informasi yang sangat  luas mengenai topik ini diperoleh dari berbagai sumber dan survei lapangan di museum terpilih dari negara modern yang memimpin pengembangan di dunia Muslim. Makalah ini merupakan sebuah upaya untuk merespon isu-isu penting dari program-program edukatif yang meningkatkan kesadaran publik tentang warisan budaya melalui desain interior dan cara menampilkan artifak dari berbagai wilayah di dunia Muslim yang telah diupayakan di berbagai museum di berbagai belahan dunia. Diharapkan, terdapat kontribusi signifikan terhadap subjek revivalisasi arsitektur Islam di dunia modern. Kata kunci: seni dan arsitektur Islam, museum, modernitas dan warisan budaya, program konservasi, aktivitas edukatif